2010
DOI: 10.1111/j.1600-0765.2010.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of salivary levels of mucin and amylase in chronic periodontitis patients

Abstract: Periodontitis induces an increase in the output of proteins, including mucin and amylase, thereby enhancing the protective potential of saliva, but this is accompanied by a decrease in flow rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 20 publications
14
71
2
7
Order By: Relevance
“…Our study is in accordance with other studies which showed an increase in amylase levels in patients with gingivitis and periodontitis [5,13,16,17].…”
Section: Collection Of Salivasupporting
confidence: 93%
See 4 more Smart Citations
“…Our study is in accordance with other studies which showed an increase in amylase levels in patients with gingivitis and periodontitis [5,13,16,17].…”
Section: Collection Of Salivasupporting
confidence: 93%
“…Salivary amylase is a calcium containing metalloenzyme that catalyses the hydrolysis of α [1,4] glycosidic bonding between glucose residues of polysaccharides such as starch, glycogen and dextrins [5,11]. In addition to its digestive action, α-amylase is also In the present study, an evaluation of mucins in unstimulated saliva was performed in healthy, gingivitis and chronic periodontitis subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations